2017
DOI: 10.5271/sjweh.3647
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysregulation in burnout and depression: evidence for the central role of exhaustion

Abstract: Objectives Given the important role of the autonomic nervous system (ANS) in stress regulation, astonishingly little is known about ANS functioning in burnout, a condition arising after prolonged exposure to work-related stress. The current study sought to investigate ANS modulation, as indexed by vagally-mediated heart rate variability (HRV), in relation to burnout symptomatology to (i) distinguish associations between the three dimensions of burnout [emotional exhaustion (EE), cynicism, reduced personal acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 64 publications
8
33
0
Order By: Relevance
“…Interestingly, we did not find associations between resting vagally mediated HRV and burnout symptomatology. The results of the few existing previous studies investigating this association have been inconclusive with some evidence suggesting reductions in vagally mediated HRV associated with the MBI total score (de Vente, van Amsterdam, Olff, Kamphuis, & Emmelkamp, 2015), while others have reported no association (Jönsson et al, 2015;van Doornen et al, 2009;Zanstra, Schellekens, Schaap, & Kooistra, 2006) or only with respect to specific sub-dimensions of this measure (Kanthak et al, 2017). Based on this small number of studies it would be premature to draw conclusions on burnout-associated modulations in vagal function.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we did not find associations between resting vagally mediated HRV and burnout symptomatology. The results of the few existing previous studies investigating this association have been inconclusive with some evidence suggesting reductions in vagally mediated HRV associated with the MBI total score (de Vente, van Amsterdam, Olff, Kamphuis, & Emmelkamp, 2015), while others have reported no association (Jönsson et al, 2015;van Doornen et al, 2009;Zanstra, Schellekens, Schaap, & Kooistra, 2006) or only with respect to specific sub-dimensions of this measure (Kanthak et al, 2017). Based on this small number of studies it would be premature to draw conclusions on burnout-associated modulations in vagal function.…”
Section: Discussionmentioning
confidence: 94%
“…Recent public health focus on occupational burnout and stress resiliency has prompted further investigation into the role of the autonomic system in cognitive performance. Increasing number of recent studies have suggested that burnout is related to autonomic dysfunction during excessive stress (Lennartsson et al, 2016; Kanthak et al, 2017; May et al, 2018; Zhang et al, 2018; Traunmuller et al, 2019). However, despite these concerning observations, the effects of autonomic state on cognitive performance have not been fully defined, and some degree of increased stress may actually be desired for task performance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, children born very preterm are endowed with immature organs and are exposed to several illness-related adversities and invasive treatments Roberts and Dalziel, 2006). Later in their lives, very preterm children are more likely to suffer from physical disorders and psychological disturbances, such as depression, burnout, and anxiety disorders (Aarnoudse-Moens et al, 2009;Aylward, 2005;, which, in turn, may be associated with alterations in autonomic function (Kanthak et al, 2017;Licht et al, 2008;van Gestel and Steier, 2011). Compared to their peers born at term, infants born preterm show decreased HRV right after birth and at theoretical term (Landrot et al, 2007;Patural et al, 2008).…”
Section: Introductionmentioning
confidence: 99%